1970
DOI: 10.2134/agronj1970.00021962006200040024x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Ultraviolet Radiation on the Persistence of Methyl Parathion and DDT in Soils1

Abstract: The effect of temperature and ultraviolet (uv) radiation on the persistence of methyl parathion (o,o‐dimethylo, p‐nitrophenyl phosphorothionate) and DDT [2,2 bis(pchlorophenyl)‐l,l,l‐trichloroethane] in soils was studied using controlled environmental conditions. Biologically effective uv radiation (300 to 400 nm) was used. Three alkaline soil types were used in the study: Houston Black clay, Pima silty clay, and Pinal gravelly loam. Soils in petri dishes were treated with a mixture of methyl parathion and DDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Surface soil temperatures of 60 °C have been measured in central Texas. Lahser and Applegate (1966) and Baker (1970) have also reported low recoverable quantities of ddt in soils from Presidio, Tex., and have indicated that volatilization was a major contributor to the loss of ddt.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Surface soil temperatures of 60 °C have been measured in central Texas. Lahser and Applegate (1966) and Baker (1970) have also reported low recoverable quantities of ddt in soils from Presidio, Tex., and have indicated that volatilization was a major contributor to the loss of ddt.…”
Section: Resultsmentioning
confidence: 96%
“…Previous experiments (Allen et al, 1954;Edwards, 1964;Lichtenstein, 1958) showed that almost all of the DDT residue in soils could be recovered in the upper 6 in. Lahser and Applegate (1966) and Baker (1970) have also reported low recoverable quantities of DDT in soils from Presidio, Tex., and have indicated that volatilization was a major contributor to the loss of DDT. Toxaphene. The watersheds studied here are situated o n a Vertisol (Houston Black clay), which consist of 50 t o 60% clay and which is predominately montmorillonitic.…”
Section: Resultsmentioning
confidence: 97%
“…The DDD and DDE metabolites come from the dehydrochlorination of DDT and their physical and chemical properties are similar [18]. The dehydrochlorination and other types of catalyzed reactions that result in a change of the chemical structure are possible by enzymes, expressed by resistant insects and some species of bacteria and fungi [13,19,20], and a photooxidation mechanism of DDT and DDE has also been discovered [1,11,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been known for some time that exposure to radiation of the ultraviolet wavelength may affect biological systems and pesticides. Many com-,on herbicides exhibit their principal electronic absorption maxima in the ultraviolet region (200-400 nm) (7) and photodecomposition by ultraviolet light has been shown to occur in a number of pesticides (4,8,12) Including 2,4-D (9). The latter was found to decompose rapidi in the presencQ of water and ultraviolet irradiation at a wavelength of 254 nm.…”
Section: Introductionmentioning
confidence: 99%